ANALISIS BORAKS PADA TAHU YANG DIPRODUKSI DI KOTA MANADO - Triastuti, Endang; Fatimawali, Fatimawali; Runtuwene, Max R.J. (PHARMACON, 2013)
ABSTRACK Tofu is a food made by coagulating soy juice and then pressing the resulting curds into soft white blocks. The use of food additive in food process needs to be aware. Borax were restricted to be used, it cause brain damage, liver, and kidney. Prolonged use may cause death. The objectives of this research was to find out the presence of borax in tofu which produced in Manado city. Investigated tofu were sample A (Bahu), B (Batukota I), C (Batukota II), D (Kleak), and E (Pakowa). Borax were evaluated by flame test, curcuma paper color test, turmeric color test and spectrophotometry UV-vis. The results shows that there were five samples that did not contains borax using flame test, curcuma paper test, turmeric paper test and Spectrophotometry UV-Vis analysis. Â  Key words : Borax, Tofu, Qualitative analysis, Spectrophotometry UV-Vis, Manado.